The Influence of 1-Methylcyclopropene on the Quality Parameters of Idared Apples after 8 Weeks of Storage Simulating Long-Distance Transportation - Kazimierz Tomala; Dominika Guzek; Dominika Głąbska; Maria Małachowska; Tomasz Krupa; Krystyna Gutkowska (Agronomy, 2021)
1-Methylcyclopropene (1-MCP), being applied in postharvest treatment of apples as an inhibitor of ethylene perception, contributes to improved quality of apples during 6 weeks of simulated long-distance transportation, but it was not studied if this period may be prolonged. The aim of the present study was to assess the possibility to apply 1-MCP treatment to maintain the quality of Idared apples for long-distance transportation prolonged for 8 weeks. The 1-MCP treatment was applied either alone, or combined with modified atmosphere packaging (MAP) in selected gas permeability bags and was compared with control group. Postharvest, the storage in Ultra Low Oxygen (ULO) chamber was applied (3 periods: 0, 10, or 20 weeks), followed by simulated long distance transportation (storage duration of 8 weeks) and simulated distribution (4 periods: 0, 5, 10, or 15 days). Each studied group (36 groups: 3 postharvest treatments × 3 storage periods × 4 distribution periods) constituted 4 batches with 10 random apples each. After simulated distribution period, each sample was analyzed to assess the differences of firmness, total soluble solids (TSS) and titratable acidity (TA). The applied treatment influenced observed values of firmness, TSS and TA within each applied storage duration and duration of distribution (p < 0.05). For the majority of the studied durations of storage and distribution, the highest values of firmness, TSS and TA were observed for the samples from the group of 1-MCP applied combined with MAP, while only for some of them, the highest values of firmness and TA, but not TSS, were observed for the samples from the group of 1-MCP applied alone. It may be concluded that applying 1-MCP in the case of Idared apples for long-distance transportation allows prolonging it to 8 weeks without decreasing quality of fruits. Applying 1-MCP combined with MAP allows obtaining even better results than 1-MCP alone, after 8 weeks of transportation. It may be recommended to apply 1-MCP combined with MAP in order to slow the ripening process and to maintain the quality of apples during a long-distance transportation.